Three‐phase qZ‐source inverter with fault tolerant capability. Issue 14 (1st November 2017) - Pires, Vitor Fernão; Foito, Daniel; Cordeiro, Armando
Abstract : The requirement of three‐phase inverters with high reliability capability is considered important in several applications. Most of the adopted fault‐tolerant solutions use classical three‐phase voltage source inverters (VSI) with redundant controlled power devices or modified control strategies for acceptably degraded performance in the event of a failure yielding the loss of devices. This work proposes the use of a fault‐tolerant converter based on the quasi‐Z‐source inverter (qZSI). This inverter presents important features such as boost capability and not requires dead time circuits. These features associated to the proposed topology results in a converter with high reliability and fault‐tolerant capability. The proposed topology is designed to allow the reconfiguration of the converter after a power switch failure, using only two legs in the faulty mode. Additionally, this topology avoids extra inductors, capacitors and active power switches for the fault‐tolerant condition. A current controller associated to a vectorial voltage modulator is used to control the proposed topology, which results in three‐phase balanced AC currents with reduced total harmonic distortion even in faulty condition. The performance of this solution is confirmed through experimental results obtained from a laboratory prototype.